2017
DOI: 10.17221/143/2016-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Tolfenamic acid and meloxicam both provide an adequate degree of postoperative analgesia in dogs undergoing ovariohysterectomy

Abstract: This study was aimed at comparing the postoperative analgesic effects of tolfenamic acid and meloxicam in dogs undergoing ovariohysterectomy. Ovariohysterectomy was performed in 24 female dogs. All dogs were administered pre-anaesthetic medication comprised of 0.02 mg/kg i.m. acepromazine, and general anaesthesia was induced with i.v. propofol (4-6 mg/kg) and maintained with 1.5-2.0% isoflurane. Dogs were divided into three groups (n = 8). Following induction of anaesthesia, group C received 0.05 ml/kg sterile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
(41 reference statements)
0
1
1
1
Order By: Relevance
“…All the selected animals have no significant differences in detail (BCS, Age, and Weight). The duration of surgery for OVH in this study was less than those reported by Acharya et al ( 1) that was 49.4 ± 0.59 minutes (VMA) and 26.2 ± 0.76 minutes (RFA), Hu et al (13) was 37.28 ± 5.81 (VMA) min, Sharda et al (22) was 44.25 ± 3.50 (VMA) and 40.50 ± 2.88 (RFA). The variation in the duration of surgery might be due to the age, weight of the animals being operated and experience of the surgeons performing surgery.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…All the selected animals have no significant differences in detail (BCS, Age, and Weight). The duration of surgery for OVH in this study was less than those reported by Acharya et al ( 1) that was 49.4 ± 0.59 minutes (VMA) and 26.2 ± 0.76 minutes (RFA), Hu et al (13) was 37.28 ± 5.81 (VMA) min, Sharda et al (22) was 44.25 ± 3.50 (VMA) and 40.50 ± 2.88 (RFA). The variation in the duration of surgery might be due to the age, weight of the animals being operated and experience of the surgeons performing surgery.…”
Section: Discussioncontrasting
confidence: 67%
“…13) that was 23.3 ± 1.9 bpm and 25.3 ± 1.8 bpm respectively but respiration rate after 24 hrs was 27.6 ± 3.2 bpm that was slightly lower. Stretching and severing of ovarian ligament are painful procedures in both methods, significantly increased HR and RR were found during severing of suspensory ligament and cervix in the flank approach.…”
mentioning
confidence: 85%
“…Antiinflamasi tolfenamic acid diinjeksi dengan dosis 0,1 ml/kg/bb. Tolfenamic acid adalah obat antiinflamasi non-steroid dari keluarga fenamat dan memiliki sifat anti-inflamasi, analgesik dan antipiretik, pada anjing tolfenamic acid cepat diabsorsi (Hu et al, 2017).…”
Section: Pembahasanunclassified